Hostages of hate - Dixon, Franklin W. (New York : Pocket Books, 1987)
The kidnapping of Frank Hardy's girlfriend at an antiterror convention in Washington, D.C., sends the brother sleuths running straight into a terrorist deathtrap.
'An Archway paperback.'
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: Mystery -- Fiction; Detective and mystery stories; Young adult fiction